Metal ion coordination toughened liquid acrylate resin and preparation method thereof

By introducing a coordination system of metal ion-promoters into the liquid acrylate resin, crosslinking between molecular chains is promoted, the problem of poor toughness of existing resins is solved, and its impact resistance and recyclability are significantly improved.

CN119775476AActive Publication Date: 2025-04-08TONGXIANG FRONTIER NEW MATERIALS RES INST +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411947726.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-08
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

The existing liquid acrylate resin has poor toughness, is difficult to withstand large impact loads, and is prone to brittle fracture, which limits its further development in the fields of composite materials, 3D printing, etc.

Method used

Through coordination reaction, metal ions are bonded to resin accelerator to form a coordination system of metal ions-accelerator, and introduced into the polymerization reaction of liquid acrylate resin to promote cross-linking between molecular chains and improve the toughness and impact resistance of the resin.

Benefits of technology

It significantly improves the comprehensive mechanical properties of liquid acrylate resin, improves its compression and impact resistance, and ensures good recyclability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005214108680000011
    Figure HDA0005214108680000011
  • Figure HDA0005214108680000012
    Figure HDA0005214108680000012
  • Figure HDA0005214108680000021
    Figure HDA0005214108680000021
Patent Text Reader

Abstract

A preparation method of the metal ion coordination toughened liquid acrylate resin comprises the following steps: adding an accelerant into an alcohol solvent, then adding a metal coordination substance, carrying out condensation reflux stirring dissolution, adding peroxide, carrying out a heating stirring reaction, and carrying out post-treatment to obtain a metal ion coordination accelerant; adding a methyl methacrylate monomer and an acrylic acid monomer into the reaction container, heating and stirring in a protective atmosphere, and cooling; and adding a metal ion coordination accelerator, stirring, adding an oxygen polymerization inhibitor, and uniformly stirring to obtain the metal ion coordination toughened liquid acrylate resin. According to the invention, the metal ions and the resin accelerator are bonded by adopting a coordination reaction, and then the obtained metal ion-accelerator coordination system is introduced into a liquid acrylate resin polymerization reaction, so that the mechanical strength and impact resistance of the acrylate resin can be remarkably improved, and the acrylate resin has good recoverability and wide applicability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of functional materials, and in particular relates to a metal ion coordinated toughened liquid acrylic resin and a preparation method thereof. Background Art

[0002] Liquid acrylic thermoplastic resins are widely used in composite materials, 3D printing, optical components and other fields due to their excellent mechanical properties, weather resistance, light transmittance, recyclability, processability and weldability. With the rapid development of the above fields, the demand for liquid acrylic resins has increased significantly, showing huge market potential.

[0003] However, the toughness of liquid acrylic resins is generally poor, which makes it difficult for them to withstand large impact loads and prone to brittle fracture, which seriously hinders their further development and application. Further design to improve the impact resistance of liquid acrylic resins and then prepare liquid acrylic thermoplastic resins with excellent toughness is an important issue that needs to be solved at present. Summary of the invention

[0004] The main purpose of the present invention is to provide a liquid acrylic resin toughened by metal ion coordination to address the problems and shortcomings of existing acrylic resins, which can significantly improve the impact resistance of acrylic resins and have good recyclability and wide applicability.

[0005] To achieve the above object, the technical solution adopted by the present invention is:

[0006] A method for preparing a liquid acrylic resin toughened by metal ion coordination comprises the following steps:

[0007] 1) Synthesis of metal ion coordination promoter:

[0008] The promoter is added to an alcohol solvent, and then a metal coordination compound is added, and the mixture is condensed, refluxed and stirred until the metal coordination compound is completely dissolved, and peroxide is added for heating and stirring reaction, and post-processing is performed to obtain a metal ion coordination promoter;

[0009] 2) Preparation of metal ion coordinated liquid acrylate resin:

[0010] Add methyl methacrylate monomer and acrylic monomer into a reaction container, heat and stir under a protective atmosphere, and cool down; then add a metal ion coordination accelerator, stir, add an oxygen inhibitor, stir evenly, and cool to room temperature to obtain the metal ion coordinated toughened liquid acrylic resin.

[0011] In the above scheme, the accelerator can be selected from N,N-dimethylaniline, N,N-diethylaniline or N,N-dimethyl-p-toluidine.

[0012] In the above scheme, the alcohol solvent can be selected from one or more of ethanol, methanol, ethylene glycol, isopropanol and the like.

[0013] In the above scheme, the solid-liquid ratio of the promoter to the alcohol solvent is 1g:3-5mL.

[0014] In the above scheme, the metal ligand can be selected from one or more of ferric chloride, ferrous chloride, zinc chloride, cupric chloride, chromium chloride, ferric nitrate, zinc nitrate, cupric nitrate, silver nitrate, etc.; the added amount thereof is 0.5-5wt% of the mass of the accelerator, preferably 1.5-2.5wt%.

[0015] In the above scheme, the temperature of the condensation reflux stirring is 50 to 80° C. and the time is 15 to 30 minutes.

[0016] Furthermore, the temperature used for the condensation reflux stirring is 65-75°C.

[0017] In the above scheme, the peroxide can be selected from one or more of dibenzoyl peroxide, ammonium persulfate, potassium persulfate, etc.; the added amount thereof is 0.5-1.5wt% of the mass of the accelerator; preferably 0.8-1.2wt%.

[0018] In the above scheme, the temperature of the heating and stirring reaction in step 1) is 55 to 65° C. and the time is 2 to 6 hours.

[0019] In the above scheme, the post-treatment includes: diluting with water, filtering to obtain precipitate, and vacuum drying.

[0020] In the above scheme, the solid-liquid ratio of the promoter introduced in step 1) to water is 1 g:15-25 mL.

[0021] In the above scheme, the temperature used for vacuum drying is 55 to 65° C., the vacuum degree is -0.06 to -0.1 MPa, and the time is 8 to 12 hours.

[0022] In the above scheme, the acrylic monomer can be selected from one or more of acrylic acid, methacrylic acid, methyl acrylate, butyl acrylate, etc., and the amount thereof is 10-25wt% of the mass of methyl methacrylate monomer; preferably 14-16wt%.

[0023] In the above scheme, the heating and stirring treatment in step 2) is carried out at a temperature of 70 to 90° C. for 2 to 4 hours, and then the temperature is lowered to 35 to 45° C.; preferably, the temperature is stirred at 75 to 85° C. for 2.5 to 3.5 hours.

[0024] In the above scheme, the amount of the metal ion coordination promoter is 0.1-1 wt % of the mass of the methyl methacrylate monomer, preferably 0.4-0.6 wt %.

[0025] In the above scheme, the 30 to 60 minutes in step 2) is preferably 35 to 45 minutes.

[0026] In the above scheme, the oxygen inhibitor can be selected from one or more of tetrakis(3-mercaptopropionic acid) pentaerythritol ester, p-hydroxyanisole, methylhydroquinone, etc.; its usage accounts for 0.1-0.4wt% of the mass of methyl methacrylate monomer, preferably 0.25-0.35wt%.

[0027] The present invention also provides a curing molding method for the above-mentioned metal ion coordinated toughened liquid acrylic resin and its composite material, comprising the following steps: adding an initiator to the obtained metal ion coordinated liquid acrylic resin, stirring at room temperature, vacuum degassing, then pouring it or compounding it with a fiber reinforced material, curing it at room temperature, and obtaining a corresponding resin molding specimen or a fiber reinforced thermoplastic composite material.

[0028] In the above scheme, the initiator can be selected from dibenzoyl peroxide, etc., and its usage accounts for 0.2-0.4% of the mass of the metal ion coordinated liquid acrylate resin.

[0029] In the above scheme, the stirring time at room temperature is 10 to 30 minutes.

[0030] In the above scheme, the vacuum degree used in the vacuum degassing is -0.06 to -0.08 MPa, and the degassing time is 5 to 10 minutes.

[0031] In the above scheme, the room temperature curing time is 6 to 8 hours.

[0032] Furthermore, the fiber reinforcement material is 1 to 2 times the mass of the liquid acrylic resin toughened by metal ion coordination.

[0033] The present invention also provides a method for recycling the above-mentioned resin molded specimens or fiber-reinforced thermoplastic composite materials, comprising the following steps: dissolving the obtained resin molded specimens or fiber-reinforced thermoplastic composite materials in an organic solvent (acetone, etc.), separating the fibers from the matrix resin by filtering or centrifuging after complete dissolution, washing the fiber surface with a pure solvent or water, and then recovering and surface treating the fiber for the production of new composite materials; precipitating the thermoplastic resin component in the solution by evaporation, precipitation or heating, and purifying the component to obtain a regenerated thermoplastic resin material, which can be re-granulated and processed.

[0034] The fibers recycled by the above method can avoid thermal degradation or mechanical damage, ensuring the high strength characteristics of the reinforcing fibers. In addition, the matrix resin selectively dissolved by the solvent has a high purity, effectively ensuring its performance.

[0035] The principle of the present invention is:

[0036] The present invention first bonds metal ions to a resin promoter through a coordination reaction, and then introduces the resulting metal ion-promoter coordination system into a polymerization reaction of a liquid acrylic resin, which can effectively promote the establishment of coordination crosslinking between resin molecular chains, increase the intermolecular force, form a crosslinking effect between polyacrylate macromolecules, and significantly improve the toughness of the resulting resin product, improve the impact resistance, and at the same time ensure good recyclability.

[0037] Compared with the prior art, the present invention has the following beneficial effects:

[0038] 1) The present invention first bonds metal ions with resin accelerators through a coordination reaction to prepare metal ion coordination accelerators, and then introduces the metal ion coordination accelerators into the preparation system of liquid acrylic resin, which can significantly improve the comprehensive mechanical properties of the obtained resin;

[0039] 2) The metal ion coordination accelerator of the present invention can effectively increase the cross-linking effect between acrylic resin molecules and effectively inhibit the occurrence of side reactions, thereby simultaneously improving the compression performance and impact resistance of the obtained resin products and ensuring good recyclability;

[0040] 3) The preparation method involved in the present invention is relatively simple and the reaction conditions are relatively mild, which is suitable for promotion and application, and can be applied to the fields of aerospace, automobiles, marine ships, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 The morphology of a is the conventional liquid acrylic resin obtained in Comparative Example 1, and b is the metal ion coordinated liquid acrylic resin obtained in Example 1;

[0042] Figure 2 The infrared spectra of the metal ion coordinated liquid acrylic resin obtained in Example 1 and the traditional liquid acrylic resin obtained in Comparative Example 1;

[0043] Figure 3 The compressive strength and impact toughness test results of the metal ion coordinated liquid acrylic resin obtained in Example 1, the traditional liquid acrylic resin obtained in Comparative Example 1, and the iron coordinated liquid acrylic resin obtained in Comparative Example 2;

[0044] Figure 4 This is a photo of the chemical recovery of the metal ion coordinated liquid acrylic resin obtained in Example 1. DETAILED DESCRIPTION

[0045] The applicant will further explain the present invention in detail below in conjunction with specific embodiments so that those skilled in the art can more clearly understand the present invention. However, the following content should not be construed as limiting the scope of protection of the claims of the present invention.

[0046] The chemical reagents and solvents used in the examples are all analytically pure. The stirring is carried out using a magnetic stirrer.

[0047] In the following embodiments, the preparation method of the metal ion coordinated toughened liquid acrylic resin comprises the following steps:

[0048] 1) Synthesis of metal ion coordination promoter;

[0049] Add 100g of accelerator (N,N-dimethylaniline) to a reagent bottle containing 500mL of ethanol, then add a metal coordination agent with a accelerator content of 0.5-5wt%, and reflux under condensation and stirring at 50-80°C; after the metal coordination agent is completely dissolved, add a peroxide with a accelerator content of 0.5-1.5wt%, stir and react at 60°C for 2-6h, add 1500-2500mL of deionized water, filter and obtain a precipitate, evacuate to -0.06--0.1MPa in a vacuum drying oven at 55-65°C, and dry for 8-12h to obtain a metal ion coordination accelerator;

[0050] 2) Preparation of metal ion coordinated liquid acrylate resin;

[0051] 100 g of methyl methacrylate monomer is added to a three-necked flask, and an acrylic monomer with a monomer content of 10 to 25 wt% is added, a nitrogen atmosphere is introduced, and the mixture is stirred at 70 to 90° C. for 2 to 4 hours, and the temperature is lowered to 35 to 45° C., and a metal ion coordination accelerator with a monomer content of 0.1 to 1 wt% is added, and the stirring is continued for 30 to 60 minutes, and an oxygen inhibitor with a monomer content of 0.1 to 0.4 wt% is added, and the mixture is stirred evenly and then cooled to room temperature to obtain a metal ion coordinated liquid acrylic resin;

[0052] 3) Curing and molding of metal ion coordinated liquid acrylate resin and its composite materials;

[0053] Add 0.2-0.4 wt% of dibenzoyl peroxide to the liquid resin obtained in step 2, stir at room temperature for 10-30 minutes, place it in a vacuum device, evacuate to a vacuum gauge pressure of -0.06-0.08 MPa, maintain for 5-10 minutes to remove bubbles in the resin, then pour it into a mold or compound it with a fiber-reinforced material, place it at room temperature to cure for 6-8 hours, and demold to obtain a resin casting or a fiber-reinforced thermoplastic composite material.

[0054] Furthermore, the metal ligand added in step 1) is one or a mixture of ferric chloride, ferrous chloride, zinc chloride, cupric chloride, chromium chloride, ferric nitrate, zinc nitrate, cupric nitrate, and silver nitrate, and the added amount is 2wt% of the accelerator.

[0055] Furthermore, in step 1), the mixture is condensed and refluxed with stirring at 70°C.

[0056] Furthermore, the peroxide added in step 1) is one or a mixture of dibenzoyl peroxide, ammonium persulfate, potassium persulfate, and the added amount is 1wt% of the content of the accelerator. Others are the same as those in one of the first to third embodiments.

[0057] Furthermore, in step 1), the reaction was stirred at 60° C. for 4 h, and 2000 mL of deionized water was added.

[0058] Furthermore, in step 1), the vacuum is drawn to -0.08 MPa in a vacuum drying oven at 60°C.

[0059] Furthermore, the acrylic monomer added in step 2) is one or a mixture of acrylic acid, methacrylic acid, methyl acrylate, and butyl acrylate, and the added amount accounts for 15 wt % of the monomer content.

[0060] Further, in step 2), stirring is carried out at 80° C. for 3 h.

[0061] Furthermore, in step 2), 0.5 wt % of a metal ion coordination promoter was added and stirring was continued for 40 min.

[0062] Furthermore, in step 2), an oxygen polymerization inhibitor with a monomer content of 0.3 wt% is added, and the oxygen polymerization inhibitor is one or a mixture of tetrakis(3-mercaptopropionic acid) pentaerythritol ester, p-hydroxyanisole, and methylhydroquinone.

[0063] Furthermore, in step 3), the amount of dibenzoyl peroxide added is 0.3 wt %, and the mixture is stirred at room temperature for 20 min.

[0064] Furthermore, in step 3), the vacuum gauge pressure is evacuated to -0.07 MPa and maintained for 8 minutes to remove bubbles in the resin.

[0065] Furthermore, in step 3), the mixture is placed at room temperature for curing for 7 hours.

[0066] Specific embodiments include the following:

[0067] Example 1

[0068] A metal ion coordinated toughened liquid acrylic resin, the preparation method of which comprises the following steps:

[0069] 1) Synthesis of metal ion coordination promoter;

[0070] 100 g of a promoter (N,N-dimethylaniline) was added to a reagent bottle containing 500 mL of ethanol, and then ferric chloride with a promoter content of 2 wt% was added, and the mixture was condensed, refluxed and stirred at 70° C.; after the ferric chloride was completely dissolved, dibenzoyl peroxide with a promoter content of 1 wt% was added, and the mixture was stirred and reacted at 60° C. for 4 h, and 2000 mL of deionized water was added, and a precipitate was obtained after suction filtration, and dried in a vacuum drying oven (-0.08 MPa) at 60° C. for 10 h to obtain an iron ion coordination promoter;

[0071] 2) Preparation of metal ion coordinated liquid acrylate resin;

[0072] 100 g of methyl methacrylate monomer was added into a three-necked flask, and acrylic acid with a monomer content of 15 wt% was added, and a nitrogen atmosphere was introduced, and the mixture was stirred at 80° C. for 3 h, and the temperature was lowered to 40° C., and an iron ion coordination promoter with a monomer content of 0.5 wt% was added, and the stirring was continued for 40 min, and pentaerythritol tetrakis(3-mercaptopropionic acid) with a monomer content of 0.3 wt% was added, and the mixture was stirred evenly and then cooled to room temperature to obtain an iron ion coordinated liquid acrylic resin;

[0073] 3) Curing and molding of metal ion coordinated liquid acrylate resin;

[0074] To the obtained iron ion coordinated liquid acrylic resin, add 0.3wt% of dibenzoyl peroxide, which accounts for 0.3wt% of its mass, stir it at room temperature for 20 minutes, place it in a vacuum equipment, evacuate the vacuum gauge pressure to -0.07MPa, maintain it for 8 minutes to remove bubbles in the resin, then pour it into a mold, place it at room temperature to cure for 7 hours, and demold it to obtain a resin casting.

[0075] Example 2

[0076] A metal ion coordinated toughened liquid acrylic resin, the preparation method of which comprises the following steps:

[0077] 1) Synthesis of metal ion coordination promoter;

[0078] 100 g of promoter (N,N-dimethylaniline) was added to a reagent bottle containing 500 mL of ethanol, and then copper chloride with a promoter content of 2 wt% was added, and the mixture was condensed, refluxed and stirred at 70° C. After the copper chloride was completely dissolved, dibenzoyl peroxide with a promoter content of 1 wt% was added, and the mixture was stirred and reacted at 60° C. for 4 h, and 2000 mL of deionized water was added, and the precipitate was obtained by suction filtration, and dried in a vacuum drying oven (-0.08 MPa) at 60° C. for 10 h to obtain a copper ion coordination promoter;

[0079] 2) Preparation of metal ion coordinated liquid acrylate resin:

[0080] 100 g of methyl methacrylate monomer was added into a three-necked flask, and acrylic acid with a monomer content of 15 wt% was added, and a nitrogen atmosphere was introduced, and the mixture was stirred at 80° C. for 3 h, and the temperature was lowered to 40° C., and a copper ion coordination accelerator with a monomer content of 0.5 wt% was added, and the stirring was continued for 40 min, and pentaerythritol tetrakis(3-mercaptopropionic acid) ester with a monomer content of 0.3 wt% was added, and the mixture was stirred evenly and then cooled to room temperature to obtain a copper ion coordinated liquid acrylate resin;

[0081] 3) Curing and molding of metal ion coordinated liquid acrylic resin and its composite materials:

[0082] To the obtained copper ion coordinated liquid acrylate resin, 0.3 wt% of dibenzoyl peroxide was added, and the resin was stirred at room temperature for 20 minutes. The resin was placed in a vacuum device and evacuated to a vacuum gauge pressure of -0.07 MPa, which was maintained for 8 minutes to remove bubbles in the resin. The resin was then composited with a fiber-reinforced material, placed at room temperature for curing for 7 hours, and demolded to obtain a fiber-reinforced thermoplastic composite material.

[0083] Example 3

[0084] A metal ion coordinated toughened liquid acrylic resin, the preparation method of which comprises the following steps:

[0085] 1) Synthesis of metal ion coordination promoter;

[0086] Add 100g of accelerator (N,N-dimethylaniline) to a reagent bottle containing 500mL of ethanol, then add zinc chloride with a 2wt% accelerator content, and stir under condensation reflux at 70°C. After the zinc chloride is completely dissolved, add dibenzoyl peroxide with a 1wt% accelerator content, stir and react at 60°C for 4h, add 2000mL of deionized water, filter and obtain a precipitate, and dry it in a 60°C vacuum drying oven (-0.08MPa) for 10h to obtain a zinc ion coordination accelerator;

[0087] 2) Preparation of metal ion coordinated liquid acrylate resin;

[0088] 100 g of methyl methacrylate monomer was added into a three-necked flask, and acrylic acid with a monomer content of 15 wt% was added, and a nitrogen atmosphere was introduced, and the mixture was stirred at 80° C. for 3 h, and the temperature was lowered to 40° C., and a zinc ion coordination accelerator with a monomer content of 0.5 wt% was added, and the stirring was continued for 40 min, and pentaerythritol tetrakis(3-mercaptopropionic acid) with a monomer content of 0.3 wt% was added, and the mixture was stirred evenly and then cooled to room temperature to obtain a zinc ion coordinated liquid acrylate resin;

[0089] 3) Curing and molding of metal ion coordinated liquid acrylate resin;

[0090] To the obtained zinc ion coordinated liquid acrylate resin, add 0.3wt% of dibenzoyl peroxide, which accounts for 0.3wt% of its mass, stir it at room temperature for 20 minutes, place it in a vacuum equipment, evacuate it to a vacuum gauge pressure of -0.07MPa, maintain it for 8 minutes to remove bubbles in the resin, then pour it into a mold, place it at room temperature to cure for 7 hours, and demold it to obtain a resin casting.

[0091] Example 4

[0092] A metal ion coordinated toughened liquid acrylic resin, the preparation method of which comprises the following steps:

[0093] 1) Synthesis of metal ion coordination promoter;

[0094] Add 100g of promoter-N,N-dimethylaniline into a reagent bottle containing 500mL of ethanol, then add ferric chloride with a promoter content of 2wt%, and condense and reflux with stirring at 70°C. After the ferric chloride is completely dissolved, add ammonium persulfate with a promoter content of 1wt%, stir and react at 60°C for 6h, add 2000mL of deionized water, filter and obtain a precipitate, dry it in a vacuum drying oven (-0.08MPa) at 60°C for 10h, and obtain an iron ion coordination promoter;

[0095] 2) Preparation of metal ion coordinated liquid acrylate resin;

[0096] 100 g of methyl methacrylate monomer was added into a three-necked flask, and acrylic acid with a monomer content of 15 wt% was added, and a nitrogen atmosphere was introduced, and the mixture was stirred at 80° C. for 3 h, and the temperature was lowered to 40° C., and an iron ion coordination promoter with a monomer content of 0.5 wt% was added, and the stirring was continued for 40 min, and pentaerythritol tetrakis(3-mercaptopropionic acid) with a monomer content of 0.3 wt% was added, and the mixture was stirred evenly and then cooled to room temperature to obtain an iron ion coordinated liquid acrylic resin;

[0097] 3) Curing and molding of metal ion coordinated liquid acrylate resin and its composite materials;

[0098] To the obtained iron ion coordinated liquid acrylate resin, 0.3 wt% of dibenzoyl peroxide was added, and the mixture was stirred at room temperature for 20 min. The mixture was placed in a vacuum device and evacuated to a vacuum gauge pressure of -0.07 MPa, which was maintained for 8 min to remove bubbles in the resin. The resin was then composited with a fiber-reinforced material, placed at room temperature for curing for 7 h, and demolded to obtain a fiber-reinforced thermoplastic composite material.

[0099] Example 5

[0100] A metal ion coordinated toughened liquid acrylic resin, the preparation method of which comprises the following steps:

[0101] 1) Synthesis of metal ion coordination promoter;

[0102] Add 100g of promoter (N,N-dimethylaniline) to a reagent bottle containing 500mL of ethanol, then add ferric chloride with a promoter content of 2wt%, and condense and reflux with stirring at 70°C. After the ferric chloride is completely dissolved, add ammonium persulfate with a promoter content of 1wt%, stir and react at 60°C for 6h, add 2000mL of deionized water, filter and obtain a precipitate, and dry it in a vacuum drying oven (-0.08MPa) at 60°C for 10h to obtain an iron ion coordination promoter;

[0103] 2) Preparation of metal ion coordinated liquid acrylate resin;

[0104] 100 g of methyl methacrylate monomer was added into a three-necked flask, 15 wt% of methacrylic acid was added into the flask, nitrogen atmosphere was introduced, the mixture was stirred at 80° C. for 3 h, the temperature was lowered to 40° C., an iron ion coordination promoter was added with a monomer content of 0.5 wt%, the stirring was continued for 40 min, pentaerythritol tetrakis(3-mercaptopropionic acid) was added with a monomer content of 0.3 wt%, the mixture was stirred evenly and then cooled to room temperature to obtain an iron ion coordinated liquid acrylate resin;

[0105] 3) Curing and molding of metal ion coordinated liquid acrylate resin;

[0106] To the obtained iron ion coordinated liquid acrylic resin, add 0.3wt% of dibenzoyl peroxide, which accounts for 0.3wt% of its mass, stir it at room temperature for 20 minutes, place it in a vacuum equipment, evacuate the vacuum gauge pressure to -0.07MPa, maintain it for 8 minutes to remove bubbles in the resin, then pour it into a mold, place it at room temperature to cure for 7 hours, and demold it to obtain a resin casting.

[0107] Comparative Example 1

[0108] A conventional liquid acrylic resin, the preparation method of which is substantially the same as that of Example 1, except that a conventional N,N-dimethylaniline accelerator is used to replace the iron ion coordination accelerator, and the added amount is 0.5 wt % of the monomer content.

[0109] Comparative Example 2

[0110] An iron-coordinated liquid acrylic resin, the preparation method of which comprises the following steps:

[0111] 1) Preparation of metal ion coordinated liquid acrylate resin;

[0112] 100 g of methyl methacrylate monomer was added into a three-necked flask, and acrylic acid with a monomer content of 15 wt% was added, and a nitrogen atmosphere was introduced, and the mixture was stirred at 80° C. for 3 h, and the temperature was lowered to 40° C., and ferric chloride with a monomer content of 0.01 wt% and N,N-dimethylaniline with a monomer content of 0.5 wt% were added, and the stirring was continued for 40 min, and pentaerythritol tetrakis(3-mercaptopropionic acid) with a monomer content of 0.3 wt% was added, and the mixture was stirred evenly and then cooled to room temperature to obtain an iron ion coordinated liquid acrylic resin;

[0113] 2) Curing and molding of metal ion coordinated liquid acrylic resin;

[0114] To the obtained iron ion coordinated liquid acrylic resin, add 0.3wt% of dibenzoyl peroxide, which accounts for 0.3wt% of its mass, stir it at room temperature for 20 minutes, place it in a vacuum equipment, evacuate the vacuum gauge pressure to -0.07MPa, maintain it for 8 minutes to remove bubbles in the resin, then pour it into a mold, place it at room temperature to cure for 7 hours, and demold it to obtain a resin casting.

[0115] The morphology of the metal ion coordinated liquid acrylic resin obtained in Example 1 of the present invention and the traditional liquid acrylic resin is shown in the figure below: Figure 1 As shown by Figure 1 It can be seen that both the conventional liquid acrylic resin and the metal ion coordinated liquid acrylic resin can be cured normally. The conventional liquid acrylic resin is light yellow after curing, while the metal ion coordinated liquid acrylic resin is slightly yellow due to Fe 3+ The presence of metal ion coordination accelerators shows purple after curing, and the surface of the resin is smooth without obvious defects after curing, indicating that good curing of the resin can still be achieved after adding metal ion coordination accelerators.

[0116] The infrared spectra of the metal ion coordinated liquid acrylic resin obtained in Example 1 of the present invention and the traditional liquid acrylic resin are as follows: Figure 2 As shown by Figure 2 It can be seen that the infrared spectrum of the metal ion coordinated liquid acrylic resin in Example 1 appears at 693 cm -1 The new absorption peak is the Fe-N coordination bond absorption peak, indicating that the metal ions are successfully coordinated with the promoter.

[0117] The compressive strength and impact toughness of the metal ion coordinated liquid acrylic resin obtained in Example 1 of the present invention, the conventional liquid acrylic resin obtained in Comparative Example 1, and the iron coordinated liquid acrylic resin obtained in Comparative Example 2 are as follows: Figure 3 As shown by Figure 3It can be seen that the compression strength and impact toughness of the metal ion coordinated liquid acrylic resin in Example 1 are respectively increased by 30% and 32% compared with the traditional liquid acrylic resin, indicating that the strength and toughness of the metal ion coordinated resin are significantly improved. The compression strength of the metal ion coordinated liquid acrylic resin prepared by directly introducing metal chloride in Comparative Example 2 is reduced by 30% and the impact toughness is increased by 6% compared with the traditional liquid acrylic resin, indicating that the comprehensive mechanical properties of the resin are reduced when the metal chloride is directly used for coordination.

[0118] The chemical recovery photo of the metal ion coordinated liquid acrylic resin obtained in Example 1 of the present invention is as follows Figure 4 As shown by Figure 4 It can be seen that the metal ion coordinated liquid acrylic resin in Example 1 can be completely dissolved after adding a proper amount of organic solvent (eg, acetone), indicating that the metal ion coordinated liquid acrylic resin can be chemically recycled and reused through a solvent method.

[0119] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0120] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

[0121] The present invention is not limited to the above-mentioned embodiments. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications are also considered to be within the scope of protection of the present invention. The contents not described in detail in this specification belong to the prior art known to professional and technical personnel in this field.

Claims

1. A method for preparing a liquid acrylic resin toughened by metal ion coordination, characterized in that: The steps include: 1) Synthesis of metal ion coordination promoter: The promoter is added to an alcohol solvent, and then a metal coordination compound is added, and the mixture is condensed, refluxed and stirred until the metal coordination compound is completely dissolved, and peroxide is added for heating and stirring reaction, and post-processing is performed to obtain a metal ion coordination promoter; 2) Preparation of metal ion coordinated liquid acrylate resin: Add methyl methacrylate monomer and acrylic monomer into a reaction container, heat and stir under a protective atmosphere, and cool down; then add a metal ion coordination accelerator and stir, add an oxygen inhibitor and stir evenly to obtain the metal ion coordinated toughened liquid acrylic resin.

2. The preparation method according to claim 1, characterized in that: The accelerator is N,N-dimethylaniline, N,N-diethylaniline or N,N-dimethyl-p-toluidine.

3. The preparation method according to claim 1, characterized in that: The metal coordination compound is one or more of ferric chloride, ferrous chloride, zinc chloride, cupric chloride, chromium chloride, ferric nitrate, zinc nitrate, cupric nitrate and silver nitrate; and the added amount thereof is 0.5-5wt% of the mass of the accelerator.

4. The preparation method according to claim 1, characterized in that: The peroxide is one or more of dibenzoyl peroxide, ammonium persulfate and potassium persulfate; and the added amount thereof is 0.5-1.5wt% of the mass of the accelerator.

5. The preparation method according to claim 1, characterized in that: The heating and stirring treatment in step 1) is carried out at a temperature of 55 to 65° C. and for a time of 2 to 6 hours.

6. The preparation method according to claim 1, characterized in that: The acrylic monomer is one or more of acrylic acid, methacrylic acid, methyl acrylate and butyl acrylate, and the amount of the acrylic monomer is 10-25 wt % of the mass of the methyl methacrylate monomer.

7. The preparation method according to claim 1, characterized in that: Step 2) The heating and stirring treatment is carried out at a temperature of 70 to 90° C. and for a time of 2 to 4 hours.

8. The preparation method according to claim 1, characterized in that: The amount of the metal ion coordination promoter used is 0.1-1 wt % of the mass of the methyl methacrylate monomer, preferably 0.4-0.6 wt %.

9. The curing molding method of the metal ion coordinated toughened liquid acrylic resin according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: adding an initiator to the obtained metal ion coordinated liquid acrylic resin, stirring at room temperature, vacuum degassing, then casting or compounding with a fiber reinforced material, and curing at room temperature to obtain a corresponding resin molding specimen or a fiber reinforced thermoplastic composite material.

10. A method for recovering molded test pieces obtained by the curing molding method of the metal ion coordinated toughened liquid acrylic resin according to claim 9, characterized in that: The obtained molded specimen is dissolved in an organic solvent, and then the thermoplastic matrix in the solution is precipitated by evaporation, precipitation or heating and purified to obtain a regenerated thermoplastic resin material.

Citation Information

Patent Citations

  • Method for preparing polyaniline derivative-metal complex

    CN101475686A

  • Metallic-ion crosslinking polyacrylate emulsion and preparation method thereof

    CN106632808A

  • Novel Polymerization Initiator and Polymerization process using the same

    GB1192166A

  • Cross-linked polymer and its production

    JP1999029607A